Increased thermal stability of nesquehonite (MgCO3·3H2O) in the presence of humidity and CO2: Implications for low-temperature CO2 storage. (August 2015) - Morgan, Bree; Wilson, Siobhan A.; Madsen, Ian C.; Gozukara, Yesim M.; Habsuda, Jana
Highlights: Short-term stability of nesquehonite is enhanced under humid conditions at <100 °C. Exposure to CO2 can enhance nesquehonite stability at Earth surface temperatures. Mg–CO2 –H2 O system is strongly influenced by slow kinetics and path dependence. Hydromagnesite does not form during rapid decomposition of nesquehonite. Tailored atmospheric conditions may improve stability of CO2 storage in minerals. Abstract: Nesquehonite (MgCO3 ·3H2 O) has in the past been proposed as a low-cost, long-term mineral host for CO2 . Here, stability of the phase was investigated under low temperatures (50 °C, 100 °C), moderate water vapour pressures (pH2 O = 0.02–0.04 atm) and in both open and closed experimental systems. Specifically, this study explores CO2 storage security in nesquehonite exposed to (1) atmospheric humidity, (2) self-generated humidity, and (3) humidity in simulated flue gases during ex situ carbonation. Both CO2 and N2 were used as carrier gases for H2 O vapour to establish the influence of CO2 on nesquehonite decomposition under humid conditions. Nesquehonite thermal stability was clearly enhanced under humid conditions for short-term (<20 h) in situ X-ray diffraction and thermogravimetric experiments. Formation of hydrous surface layers may impede structural H2 O release from nesquehonite; delaying dehydration and preventing subsequent decomposition. Enhanced stability of nesquehonite was also observed under a CO2 atmosphere. This study presents novel insights into the importance of temperature, pH2 O and pCO2 when considering the suitability of nesquehonite as a long-term CO2 store. Additionally, it establishes basic, previously overlooked conditions that are essential considerations when tailoring disposal, storage and ex situ carbonation to enhance CO2 stability in metastable Mg-carbonate phases.